Cocoon production and hatching rates of Branchiura sowerbyi Beddard (Oligochaeta: Tubificidae) - Nascimento,Haroldo L. S. (2008)
Branchiura sowerbyi Beddard, 1892 is a Tubificidae species abundant in tropical limnic environments and associated with sediments rich in organic matter and elevated temperatures. The present study aimed at obtaining information on laying and hatching rates of B. sowerbyi cocoons under laboratory conditions. In order to do this, specimens of B. sowerbyi were placed in beakers (250 ml) containing clay sediment and distilled water and kept at 25ºC. The obtained cocoons were placed in beakers of 100 ml and kept in conditions similar to the mature individuals. Fifty seven cocoons were collected, with a mean of 0.13 cocoons·individual-1·day-1 and 1.21 (±0.08) eggs·cocoon-1. Hatching time was approximately two weeks and hatching rate was 44.93%. The results obtained were different from the ones found by other authors for B. sowerbyi. According to the literature, different populations of the same species can present distinct biological aspects, such as the number of cocoons, hatching rates and growth.